Implementasi Kode Etik Profesi Jabatan Notaris Terhadap Notaris Yang Bekerjasama Dengan Bank - Karina Darojatun Agnia (Officium Notarium, 2021)
Notary as a profession has an association, namely the Indonesian Notary Association (INI), INI Congress stipulates a Notary Code of Ethics that regulates the behavior of Notaries in carrying out their positions. The Law and the Code of Ethics do not include prohibitions for Notaries to enter into agreements with any party, but in practice there are many cooperation agreements between Notaries and Banks which result in Notaries being dependent. The formulation of the problemd taken are First, how is the implementation of the Notary Code of Ethics for notaries who cooperate with banks. Second, how is the responsibility of the notary in upholding independence in making deeds. This is an empirical juridical research. The data used is primary data, which is supported by secondary and tertiary data through interviews, literature studies, and studies of legislation. The results of the study conclude tjat the role of a notary is very much needed by banks, this is related to the legal risk of assets pledged by debtors as credit collateral. The responsibilities of a Notary as a public official include the responsibilities of the Notary profession itself related to the deed.Key Word: Code of Ethics, Implementation, Responsibility AbstrakNotaris sebagai suatu profesi memiliki perkumpulan yaitu Ikatan Notaris Indonesia (INI), Kongres INI menetapkan Kode Etik Notaris yang mengatur perilaku Notaris dalam menjalankan jabatannya. Dalam Undang-Undang maupun Kode Etik tidak mencantumkan larangan bagi Notaris untuk mengadakan perjanjian dengan pihak manapun, namun dalam prakteknya banyak terjadi perjanjian kerjasama antara Notaris dan Bank yang mengakibatkan Notaris tidak mandiri. Rumusan Masalah yang diambil yaitu, Pertama, bagaimana implementasi Kode Etik Notaris terhadap notaris yang bekerjasama dengan bank, Kedua bagaimana tanggung jawab notaris dalam menjunjung tinggi kemandirian dalam pembuatan akta. Penelitian ini merupakan penelitian yuridis empiris. Data yang digunakan adalah data primer, yang didukung oleh data sekunder dan tersier melalui wawancara, studi pustaka, dan studi peraturan perundang-undangan. Hasil penelitian menyimpulkan, Peran Notaris sangat dibutuhkan oleh bank, hal ini berkaitan dengan risiko hukum atas harta kekayaan yang diagunkan oleh debitur sebagai agunan kredit. Tanggung jawab Notaris sebagai pejabat umum meliputi tanggung jawab profesi Notaris itu sendiri yang berhubungan dengan akta, terhadap akta yang dibuatnya Notaris wajib bertanggung jawab atas keautentikannya.Kata-kata Kunci: Kode Etik, Implementasi, Tanggung Jawab